Effect of supplementation of probiotics and prebiotics on growth, lipid profile and slaughter traits of coloured broilers during heat stress - ROUL, G; PANDA, N; MISHRA, P K; BEHERA, P C; PANIGRAHI, B; PATI, P K (The Indian Journal of Animal Sciences, 2015)
Supplementation of probiotics and/or prebiotics to coloured broilers during summer on growth, serum lipid profile and carcass traits were studied. Day-old coloured broiler chicks (180) were randomly distributed into 4 groups with 3 replicates having 15 chicks in each. The 4 dietary treatments such as T1 -control group fed with basal diet, T2 - basal diet+ probiotic @ 10 g/q feed, T3-basal diet + prebiotic (MOS) @ 4,000 ppm and T4- basal diet+probiotic @ 10 g/q and prebiotic @ 4,000 ppm. The supplementation was continued from 0 to 56 days of age during natural peak summer period. Significantly better growth rate and FCR was observed in the group supplemented with both pro- and pre-biotics than control but no difference of feed intake was observed. There was significant reduction of lipid profile like triglycerides, LDL and VLDL levels of all the supplemented groups. No difference of any of the carcass traits was observed. It is concluded that the feeding of both probiotics and prebiotics in combination to the coloured broilers during summer improved growth performance and decreased serum triglycerides levels.